Strategi Perbankan Syariah Dalam Optimalisasi Pembiayaan Berbasis Bagi Hasil (Studi Kasus Pt Bprs Al Salaam Amal Salman) - Hendra Adi Wijaya; Koesmawan Koesmawan; Jafril Khalil (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2019)
Mudharabah and musyarakah are profit-based financings at Islamic banks, both Islamic commercial banks (BUS) and Islamic people's financing banks (BPRS). The development of this financing is prolonged, recorded in the period 2005-2015 in Islamic banks the composition of profit-sharing based financing of 36% and for sale-based financing of 64%, while in Islamic people's financing banks with profit-sharing based financing composition of 14% and for sale-based financing of 86%. The purpose of this study is to determine the factors that cause low profit-based financing and determine the right strategies in optimizing profit-based financing at PT SRB Al Salaam Amal Salman, which is expected to be used by other Islamic banks. This study uses a SWOT and AHP analysis to determine internal and external factors related to the optimization of the financing. The results show that the factors causing low profit-sharing based financing include the factors of honesty and the high level of risk. The strategy to increase profit-sharing based financing is to increase the number of mudarib and partners with appropriate alternative strategies namely to increase marketing and promotion, building full trust with mudharib and partners, improving the quality of human resources, and increasing socialization and education to the community.